Reviewing Management Learning: The field and the journal. Issue 1 (February 2020) - Anderson, Lisa; Thorpe, Richard; Coleman, Charlotte
We trace the origins and development of the management learning movement that has come to be closely associated with the journal Management Learning and explain how ideas that shaped the creation of business schools influenced the inception of this field. We then examine themes and trends that have been prevalent in the field in the second half of the journal's 50-year history, through an analysis of its coverage over a 24-year period from 1994 to 2018. During this time, there has been a marked shift away from an applied focus on manager and management development towards a more theoretical perspective of the field, in keeping with trends in academic journals more generally. We focus on the journal's contribution to the scholarship of management and organisational learning through an analysis of both strong and weak themes and its most cited papers. Finally, we propose ways in which our analysis of the past might offer new ways of thinking about our scholarship and we propose a future direction for the field and the journal that connects to the original intentions to shape organisational practice in order to address broader issues of social and economic exchange.